Two new cauliflorous species of Aristolochia subseries Anthocaulicae (Aristolochiaceae) from southern Central America - Jiménez Vargas, José Esteban (2022)
Two new cauliflorous species of Aristolochia subseries Anthocaulicae from southern Central America are described and illustrated. Aristolochia guanacastensis from northwestern Costa Rica resembles A. ruiziana, from which it is distinguished by having glabrous and narrower leaves, larger flowers without a syrinx, and shorter fruits. Aristolochia povedae from the Caribbean slope of Costa Rica and Panama is similar to A. cordiflora, but it is distinguished by its smaller, suborbicular and concave perianth limb with a shallower sinus, and slightly larger fruits. Comments about their distribution, habitat, phenology, conservation status, and distinction from related species are provided, and also a key to the species of Aristolochia subseries Anthocaulicae present in Central America. Evidence that supports the synonymization of A. cruenta under A. goudotii is presented.